AN ERROR ANALYSIS ON STUDENTS’ PRONOUNCIATION IN SPEAKING - Eva Faliyanti; Ridho Mela Prasesti (INOVISH JOURNAL, 2016)
Abstract: The objective of this research is to analyze the students error pronounciation in speaking ability. The purpose of this research is to know what the factors that make error on students pronounciation and the frequency of error do by students in speaking ability. The informant of this research are the second semester students at English Education Study Programe in Muhammadiyah University of Metro. The researcher take 10 students randomly as the sample and using simple method to analyze the data. The researcher used descriptive qualitative method to explain the result of the research. In collcting the data, the researcher used 3 step, there were observation, interview and recording. After the data of the students collected, the researcher found the causes of errors on students’ pronounciation. They are internal errors that consisted of mother tongue, similiar words, slip of the tongue and errors in students’ organ of speech and external factors that consisted of laziness in speaking English, and never using English in daily activity.           Keywords : Error Analysis, Pronounciation, Speaking Ability.